Inovasi Kebijakan dalam Mengurangi Biaya Pendidikan: Strategi Berbasis Bukti untuk Meningkatkan Aksesibilitas dan Kualitas - M. Syukron Ali Amiruddin; Moh. Ansori FT; Mahrus Ali; Anim Jauhariyah (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
ABSTRACT This research aims to analyze policy innovations in reducing education costs at MTsN 9 Banyuwangi and their impact on increasing accessibility and quality of education. The research approach used is qualitative with a case study design, involving in-depth interviews, observation and document analysis as data collection techniques. The research results reveal five main findings: (1) implementation of a need-based scholarship program that provides financial assistance to underprivileged students, (2) digitalization of learning to reduce the cost of books and teaching materials, (3) collaboration with school committees and local donors in fundraising , (4) implementation of the